Carbapenem resistance in Acinetobacter pittii isolates mediated by metallo-β-lactamases. (20th December 2022) - Wunderlich, Alexander; Xanthopoulou, Kyriaki; Wille, Julia; Wohlfarth, Esther; Gerson, Stefanie; Kaase, Martin; Seifert, Harald; Higgins, Paul G
Abstract: Objectives: To characterize the genetic environment of metallo-β-lactamases (MBL) in carbapenem-resistant clinical Acinetobacter pittii isolates. Methods: Seventeen carbapenem-resistant A. pittii isolates harbouring an MBL were collected between 2010 and 2015 in Germany. Antimicrobial susceptibility testing was performed using agar dilution. Presence of MBLs was confirmed by PCR and their genetic location determined by S1-pulsed-field gel electrophoresis followed by Southern blot hybridization. Whole-genome sequencing was performed using the Miseq and MinION platforms. Isolates were typed using an ad hoc core genome MLST scheme. Conjugation into A. baumannii was tested by broth mating. Results: In 10 isolates the MBL was plasmid-encoded and in seven isolates chromosomally encoded. bla GIM-1 and bla VIM-2 were plasmid-encoded, bla VIM-4 was chromosomally encoded, while bla NDM-1 was chromosomally encoded in four and plasmid-encoded in three isolates. Seven of ten plasmids were conjugative into A. baumannii . Although most isolates were unrelated, the backbones of the MBL-encoding plasmid showed >99% similarity and only differed in the MBL-encoding area. bla NDM-1 -harbouring plasmids were highly similar to other plasmids from Acinetobacter isolates worldwide while the bla VIM-2 - and bla GIM-1 -encoding plasmids have not been described. Conclusions: These data show the existence of a promiscuous plasmid circulating in A. pittii isolates in Germany that differs only in the MBL-encoding region. Its plasmid backbone has been found globally among multiple Acinetobacter spp. These data should raise awareness of an epidemic conjugative plasmid that has independently acquired MBLs. We should also consider that future comparative plasmid analysis will look beyond solely the resistome and include the mobile elements carrying the resistance genes.